Heart rate and suicide: findings from two cohorts of 533 000 Taiwanese and 75 000 Norwegian adults. (22nd October 2015) - Chang, S.‐S.; Bjørngaard, J. H.; Tsai, M. K.; Bjerkeset, O.; Wen, C. P.; Yip, P. S. F.; Tsao, C. K.; Gunnell, D.
Abstract : Objective: To investigate the association of resting heart rate with suicide in two large cohorts. Method: The MJ cohort (Taiwan) included 532 932 adults from a health check‐up programme (1994–2008). The HUNT cohort (Norway) included 74 977 adults in the Nord‐Trøndelag County study (1984–1986), followed up to 2004. In both cohorts heart rate was measured at baseline, and suicide was ascertained through linkage to cause‐of‐death registers. Risk of suicide was estimated using Cox proportional hazards models. Results: There were 569 and 188 suicides (average follow‐up period of 8.1 and 16.9 years) in the MJ and HUNT cohorts respectively. Sex‐ and age‐adjusted hazard ratio for every 10 beat increase in heart rate per minute was 1.08 (95% Confidence Interval 1.00–1.16) and 1.24 (1.12–1.38) in the MJ and HUNT cohorts, respectively. In the MJ cohort this association was confined to individuals with a history of heart diseases vs. those without such a history ( P for interaction = 0.008). In the HUNT cohort the association did not differ by history of heart diseases and was robust to adjustment for health‐related life style, medication use, and symptoms of anxiety and depression. Conclusion: Elevated resting heart rate may be a marker of increased suicide risk.